Rapid development of robotic concept stations in ABB RobotStudio - Kopacz, Joseph R., author; Alciatore, David, advisor; Williams, John, committee member; Maciejewski, Tony, committee member (Colorado State University. Libraries, 2013)
The purpose of this thesis was to facilitate the design of various tools for Wolf Robotics to support the rapid development of concept stations. Feasibility of new parts is an integral part of design of robotic welding cells and requires a concept station. Many independent developers use virtual simulation to mitigate the risks involved when working with new parts in robotic systems. These developers desire a quick and accurate program to mock up robotic stations equipped with various welding accessories and robot positioners. The current software used by these developers requires advanced training and a large time investment. For these reasons, a quick and accurate way to create new concept cells was created. This was accomplished through the development of programmed add-ins and smart components in ABB RobotStudio. In addition to the smart component series and the add-in, user and maintenance manuals were also developed to train personnel quickly.
Keywords: ABB; welding; RobotStudio; robotic; robot